Students’ Psychological Adjustment in Normative School Transitions From Kindergarten to High School: Investigating the Role of Teacher-Student Relationship Quality - Longobardi, Claudio; Settanni, Michele; Prino, Laura Elvira; Fabris, Matteo Angelo; Marengo, Davide (Frontiers in Psychology, 2019)
School transitions require students to adapt to new challenges and situations and can increase the risk of externalizing and internalizing psychological symptoms. The teacher-student relationship seems to be a protective factor for the risk of developing psychological symptoms during school transitions. The aim of the present study is to investigate whether the quality of the teacher-student relationship predicts the decrease of internalizing and externalizing symptoms during 3 school transitions, namely: from kindergarten to primary school (T1), from primary to middle school (T2), and from middle to high school (T3). We recruited 127 kindergarten students (Mean age = 5.40, SD = 0.49), 113 5th grade primary school students (Mean age = 10.64, SD = 0.54), and 240 8th grade students (Mean age = 13.88, SD = 0.37) and their teachers (response rate = 95%). Data were collected from 2016 to 2018. Teachers filled out an anonymous survey, acting as informants for the students, reporting demographic details (age, gender), psychological symptoms, and quality of the teacher-student relationship. The data show that a positive teacher-student relationship quality tends to be associated with a reduction of psychological symptoms. A stable, low-conflict teacher-student relationship was confirmed as a protective factor from increased internalizing and externalizing symptoms during all normative school transitions. Furthermore, we see that an increase in teacher-student conflict during the transitions from primary to middle school, and from middle to high school is linked to an exacerbation in students’ externalizing symptoms during the first year of attendance of the new school. Our study confirms the importance of the teacher-student relationship in reducing psychological symptoms associated with school transitions, in every type of transition, favoring an improved psychological adjustment to the new environment. A positive teacher-student relationship represents a protective factor for the development of students. Study limitations are discussed.